Strategi Pemasaran Susu Kedelai ASKA Menggunakan Analisis SWOT - Yusvi Diana (CV. ITTC INDONESIA, 2026)
Marketing strategy is a key issue for small agroindustry because soy milk products have a short shelf life, simple packaging, limited promotion, and intense competition from similar and substitute products. This study aims to identify the internal and external marketing factors of ASKA Soy Milk and formulate alternative strategies based on SWOT analysis. The study used a descriptive qualitative approach. The population included all actors related to ASKA soy milk marketing, while the informants were selected purposively from business managers, production and marketing employees, retailers, consumers, competitors, and suppliers. Primary data were collected through observation, interviews, and documentation, whereas secondary data were obtained from business records and relevant literature. Data were analyzed using the marketing mix framework, internal-external factor mapping, and the SWOT matrix. The findings show that ASKA has strengths in flavor variation, affordable prices, larger content volume, discounts, its own distribution facilities, and retailer networks. Weaknesses include a one- to two-day shelf life, incomplete labels, simple packaging, and promotion that has not reached final consumers optimally. Opportunities arise from healthy-drink trends, packaging technology, digital promotion, and wider market segments, while threats come from local and non-local competitors and substitute products. The recommended strategies are improving packaging and labels, expanding distribution, strengthening social media promotion, offering consumer discounts, and developing product-size variation. These strategies imply that ASKA should prioritize packaging, consumer-oriented promotion, and daily distribution management to improve competitiveness and sales sustainability.